READING TO LEARN PROGRAM TO TEACHING CRITICAL W - Udi Samanhudi; Sugiarti Sugiarti (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2013)
This study reports the effectiveness of using Reading to Learnprogramin teaching critical writing to teacher candidates in English Language Teaching Department, Sampoerna School of Education, Jakarta. The Reading to Learn program implemented in this study allows the researchers to employ principles from other theories to do with critical thinking and critical literacy important to the study. Embracing the characteristics of a case study and to some extent a program evaluation research design, data in this study were obtained from classroom observations by the two researchers, collection of samples of students’ texts in various stages of the teaching program and students’ journals written after each teaching session and interviews with the student participating in this study conducted immediately after the teaching program completed. The results revealed that students’ ability to write an English text is better than before indicated by their ability to clearly and explicitly explain details of information in the text they write which surely fulfill the standard outlined in the critical thinking theory used in this study. Key words: Reading to learn program, writing, critical thinking